FORMULASI SEDIAAN GEL DISPERSI PADAT IBUPROFEN : STUDI GELLING AGENT DAN SENYAWA PENINGKAT PENETRASI - Dwi Nurahmanto; Ifa Rosi Mahrifah; Rani Firda Nur Imaniah Azis; Viddy Agustian Rosyidi (Jurnal Ilmiah Manuntung, 2017)
ABSTRACT This study aims to determine the effect of using gelling agent and chemical penetration enhancer on the solid dispersion Ibuprofen gel in increasing the transdermal drug penetration. Inhibition of the COX-1 enzyme caused by ibuprofen in oral administration can cause side effects of gastrointestinal disorders, dyspepsia, diarrhea, upper gastrointestinal infections, nausea and bloating, resulting in a topical route to reduce side effects. The gel is prepared using hydroxy propyl methyl cellulose (HPMC) and carbopol® as gelling agents, and also propylene glycol and glycerin as chemical penetration enhancer compounds. The gel evaluation are viscosity, pH, spreadability and penetration flux rate. The value of the formula 3 penetration flux is 1.5383 ± 0.029 ug / cm2.minute, the formula 1 is 1.403 ± 0.055 ug / cm2. minute, the formula 2 is 0.756 ± 0.071 ug / cm2 minute, while the formula 4 is 0.5404 ± 0.106 ug / Cm2. minute. The amount of gelling agent concentration and chemical penetration enhancer compound effect on the value of the flux penetration